70% Ethanolic flaxseed extract enhances SaOS-2 cell proliferation in bone wound-healing model (In-Vitro) - Shaban, Sama; Mokhtar@Makhtar, Khairani Idah; Mustafa Al-Ahmad, Basma Ezzat; Mustafa, Nazih Shaban; Mohd Noor, Mohd Fadly; Ichwan, Solachuddin J. A. (2022)
Flaxseed (linum usitatissimum) known as Biji Rami in Malay; is a plant with many health promoting properties such as anti-cancer, anti-fungal, and anti-microbial health promoting activities, hence, recognized as a “super food”. As for wound healing properties, it has been confirmed that flaxseed promotes the healing of skin wounds in both in-vitro and in-vivo study models. Nonetheless, very limited studies are available looking into the effect of flaxseed on bone wound-healing. SaOS-2 is an osteoblast-like cell line which has been widely utilised in studies focussing on bone cell development including bone wound-healing. Thus, this study aims to demonstrate the ethanolic flaxseed extract wound healing activity on SaOS-2 representing the bone wound-healing model in-vitro. The process of obtaining 70% ethanolic extract was done through soxhlet extraction method, the extract in 25 μg/ml was then used to treat confluence SaOS-2 cell line which was cultured in DMEM in a 95% humidity 5% CO2 incubator. Wound healing assay or scratch assay was used to determine the wound healing activity of 70% ethanolic flaxseed extract on SaOS-2 cell line in a qualitative and quantitative manner at 18, 24, 48, 72, and 96 hours. The results illustrated the effect of 70% ethanolic extract on SaOS-2 cells showing cell proliferation activity as fast as 18 hours after treatment, the cells fully covered the wound area by 72 hours. The mean and standard error were calculated for each triplicate set of data. In conclusion, flaxseed extracted using 70% ethanol as medium of extraction successfully enhanced the cell proliferation and managed to fully heal the made-up wound on SaOS-2 cell line. Our study demonstrated that ethanolic flaxseed extract has a great potential to heal deep wounds especially the ones effecting the bone. This positive effect might be contributed by the presence of phenolic compounds in the extract.